The Life of Christopher - Joshua Mugler (Columbia University Libraries, 2021)
Christopher, a native of Baghdad who became patriarch of Antioch in about 349/960, was assassinated by Muslim rebels in 356/967 because of his loyalty to their Muslim ruler. When the Byzantines conquered Antioch two years later, his story was told in a variety of ways by those with different and competing interests. Christopher was mentioned in Byzantine histories and in Antiochian liturgies. However, by far the most extensive and detailed version of the story comes to us in the Life of Christopher, written by Ibrāhīm b. Yūḥannā, a Byzantine bureaucrat and translator who grew up in Antioch and knew Christopher when he, Ibrāhīm, was a young boy. The hagiography was originally composed in Greek and translated by its author into Arabic, but only the Arabic survives. Here I provide, for the first time, both a critical edition of the two known Arabic manuscripts and a full English translation. This text is a valuable testimony to Christian life in Antioch under both the Ḥamdānids and the Byzantines, and to the difficulties of life along the constantly shifting frontier of medieval northern Syria.